The profile of EEUSP graduates of the stricto sensu program in nursing management - Felli, Vanda Elisa Andres; Kurcgant, Paulina; Ciampone, Maria Helena Trench; Freitas, Genival Fernandes de; Oguisso, Taka; Melleiro, Marta Maria; Tronchin, Daisy Maria Rizatto; Gaidzinski, Raquel Rapone (Revista da Escola de Enfermagem da USP, 2011)
The objectives of the present study were to identify and discuss on the profile of the graduates form the stricto sensu program in Nursing Administration/Management of the University of São Paulo School of Nursing, from October 2008 to June 2011, regarding the knowledge areas the graduates worked on during their master and doctoral program. This is an exploratory, descriptive, retrospective study, using documental analysis. The study population consisted of 250 graduates, 169 of which were masters and 81 doctorates. The graduates' profile permitted to identify and discuss on the retention rate for the doctorate; the type of institution that absorbs the master and doctorate graduate and the fields they work in.